Genetic dissection of yield associated traits in a cross between cowpea and yard-long bean (Vigna unguiculata (L.) Walp.) based on DArT markers - Garcia-Oliveira, A.L.; Zate, Z.Z.; Olasanmi, B.; Boukar, O.; Gedil, Melaku A; Fatokun, C. (Springer, 2020)
Both cowpea and yard-long bean belong to Vigna unguiculata ssp. unguiculata but have diverged through human induced evolution in sub-Saharan Africa and Asia, respectively. To map the quantitative trait loci (QTLs) for yield associated traits and derive new lines that may combine the attributes of both types, we developed a F2:3 mapping population derived from a cross between cowpea line TVu2185 and yard-long bean line TVu6642. Using DArT markers, a total of 30 QTLs accounting for 1.8–13.0% phenotypic variation was detected for pod and seed traits. Some novel major QTLs for peduncle number per plant (qPeN2.2), pod length (qPoL3), seed breadth (qSB4), length (qSL7.2) and thickness (qST9) identified on chromosomes 2, 3, 4, 7 and 9, respectively, are particularly interesting and need to be validated. Moreover, we confirmed previously reported QTLs for pod length (qPoL8) and 100-seed weight (qSW8) on chromosome 8 and for seed number per pod (qSN9.2) on chromosome 9 suggesting usefulness for marker-assisted-selection purpose. Notably, some QTLs for these traits were clustered especially on chromosomes 5, 7, 8, 9 and 10 indicating the presence of the same QTL or linked loci in these regions. Moreover, the involvement of epistasis was observed for trait expressions, but compared with the main effect QTLs, the phenotypic effects of epistatic-QTLs detected were much less. The present QTL analysis may provide a useful tool for breeders to formulate efficient breeding strategy for introgression of the desirable alleles for yield related traits in cowpea using molecular markers.